Evolving open and independent ontologies. (2nd April 2007) - Castano, Silvana; Ferrara, Alfio; Montanelli, Stefano
In this paper, we address the problem of evolving open and independent ontologies, by proposing a novel ontology evolution methodology called H-CHANGE and a set of related techniques. After providing a formal definition of distributed concept, we describe; change detection techniques based on semantic matchmaking for determining the semantics of change; assimilation techniques for evolving ontology metadata according to new incoming external knowledge at different integration levels, ranging from concept merging to concept alignment. Examples of evolving OWL ontologies according to H-CHANGE are also provided.